Tiny terror : why Truman Capote (almost) wrote Answered prayers - Schultz, William Todd (Inner lives., 2011)
Truman Capote was one of the most gifted and flamboyant writers of his generation, renowned for such books as Other Voices, Other Rooms, Breakfast at Tiffany's, and his masterpiece, the nonfiction novel In Cold Blood. What has received comparatively little attention, however, is Capote's last, unfinished book, Answered Prayers, a merciless skewering of cafe society and the high-class women Capote called his "swans." When excerpts appeared he was immediately blacklisted, ruined socially, labeled a pariah. Capote recoiled--disgraced, depressed, and all but friendless. In Tiny Terror, a